Menyikat Gigi Dengan Metode Horisontal Terhadap Penurunan Skor Plak - SUKARMAN SUKARMAN (POLITEKNIK KESEHATAN KEMENKES PALEMBANG, 2014)
The accumulation of plaque that wasn’t cleaned, could form colony and ferment the carbohidrat to be acid that will cause caries. One of the early preventive measure to control the plaque was by brushing teeth regularly. horizontal method was very accepted and easy to do brushing method. The research was conducted to assess the effect of tooth brushing with horizontal method to reduction of dental plaque score. The method was experimental study with pre-post test group design. The sample of this research was 90 respondents. Each group consists of 30 respondents Were divided into 3 groups. Group A as the control group that was brushing without horizontal method, group B that was brushing with horizontal method for ½ minute, and group C that was brushing with horizontal method for 1 minute. Data were taken from the dental plaque score before and after brushing. Data were analyzed by using statistical parametric One Way ANOVA. The results showed that there were the effect of tooth brushing with horizontal method appeared significant statistically ( p<0,05). It could be concluded that toothbrushing with horizontal method had an effect on reduction of dental plaque scores.